Disease investigation of small indigenous fish species Channa punctatus of three fish markets in Mymensingh, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Studies were conducted to investigate the health condition of a small indigenous fish Channa punctatus through clinical and histopathological observations for a period of six months. The samples were collected from different fish markets of Mymensingh District. Water quality parameters viz., temperature and dissolve oxygen were recorded and, clinical and histopatlogical study were done at monthly intervals. Normal appearances were observed during the months of October to November and also February to March from the fish samples of three fish markets. In the months of December and January, fishes were more affected having scale loss, red spots, deep dermal ulcer in Sankipara Railway Crossing and Gollpukurpar markets. Histopathologically, marked necrosis, pyknosis, haemorrhage and fungal granuloma were observed in skin and muscle. Gills of fishes from Sankipara Railway Crossing and Gollpukurpar markets had found monogenetic trematode, hypertrophy, clubbing and pyknosis in December and January. Livers of the examined fishes had no pathogen and showed less pathological signs compared to other organs. Fungal granuloma, necrosis, haemorrhage and vacuoles were found in the kidney of fishes collected from Gollpukurpar market and Sankipara Rail Crossing market. The investigated species C. punctatus was found more affected in Gollpukurpar and Sankipara Rail Crossing market than the fish samples of K-R market during the month of December and January. In the other months there were reduced clinical and histological symptoms in fish of all the markets.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 268-273